THE FIRST DERIVATIVE OF APEX CARDIOGRAM AND ITS UTILIZING FOR DETERMINING SOME SYSTOLIC AND DIASTOLIC TIME INTERVALS IN MAN - NIKOLAI KOLEV (Acta Medica Iranica, 1980)
To determine the usefulness of the time intervals obtained from the first derivative of apex cardiogram (dA/dt) in assessing contraction and relaxation, 20 hemodynamically and angiographical1y investigated patients with coronary artery disease and 29 patients with hypertensive heart disease were studied. As a control group there were used 50 normal subjects. Since contraction and relaxation is dependent on preload and afterload, the time interval from R wave of electrocardiogram to the positive peak of dA/dt (R to dA/dt) and two relaxation parameters derived from negative peak dA/dt were investigated, early relaxation index (ERI) and total relaxation index (TRI). In patients with coronary artery disease all of these parameters were augmen- -- ted (R to dA/dt: 121 + 14 controls; ERI: 13.1 149 + 30 Versus + 8 - msec versus 76 + 14 msec for versus 4.3 + 5 in controls; TRI 71 + 18 for controls) and also pat ients with hypertensive heart disease s howed similar change s ( ~ to dA/ cant c orrelatio ns between these indexes a nd some i nternally par ame t e r s of myocar d i a l performance were ob s erved . These findings indicate that s ystolic and diastolic time intervals me a s ured f rom the firs t de r i v a t i v e o f apex ca r d iogr am may be used a s a reliable indices for evaluation o f contraction and relaxation independently of p r e loa d and afterload.